Engineering design of n/p-type nano heterojunctions loaded on cotton cellulose nanocrystal surface: Removal of pollutants and supercapacitors applications. (February 2023) - El-Shafai, Nagi M.; Masoud, Mamdouh S.; Ramadan, Mohamed S.; El-Mehasseb, Ibrahim
Abstract: The target of work illustrates the importance of obtaining clean water production via the engineering design of nano heterojunction between n/p-type nanomaterials loaded on the cellulose nanoparticles (NPs) surface. The various tools used for confirmation of the fabrication of the hybrid nanomaterials (HNM) such as electron microscopy (Transmission TEM and scanning SEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). In the photocatalytic and adsorption process used to clean the water from the different pollutants such as Methylene blue (MB) and Rhodamine B (RhB), the rate of photodegradation is 8.98 × 10 −4 min −1 ± 1.611 × 10 −4 and 0.011 min −1 ± 5.11 × 10 −4 for RhB and MB dye respectively. While the mixed dye (RhB-MB) is 3.374 × 10 −4 min −1 ± 1.49 × 10 −4 for RhB and 0.00829 min −1 ± 4.99 × 10 −4 for MB. The removal of imidacloprid insecticide under a visible light source, where the rate is 0.00835 min −1 ± 2.06 × 10 −4 . The removal rate of chromium (Cr +3 ) is 0.0034 ± 4.89 × 10 −4 and the efficiency of degradation was 56 %. The supercapacitor and energy storage are detected by impedance spectroscopy via the cyclic voltammetry technique. The glucose sensor is studied via spectroscopy and electrochemical techniques, also antioxidant activity is studied with the fabricated electrode. The cytotoxicity of the fabricated material is detected with the cell line. The nanocomposite is a promising candidate for water clean production, biosensor, and energy applications. Highlights: Engineering design nano-heterojunctions on cotton cellulose nanocrystal. Engineering building nanomaterial for pollutants removal (heavy metals and dyes) Biosensors and antioxidant efficiency by the modified electrode Cell@MoS2 .NiO The modified electrode of Cell@MoS2 .NiO for Supercapacitor applications